Bulk sediment 14C dating in an estuarine environment: How accurate can it be?. (2nd February 2017) - Lougheed, Bryan C.; Obrochta, Stephen P.; Lenz, Conny; Mellström, Anette; Metcalfe, Brett; Muscheler, Raimund; Reinholdsson, Maja; Snowball, Ian; Zillén, Lovisa
Abstract: Due to a lack of marine macrofossils in many sediment cores from the estuarine Baltic Sea, researchers are often forced to carry out 14 C determinations on bulk sediment samples. However, ambiguity surrounding the carbon source pathways that contribute to bulk sediment formation introduces a large uncertainty into 14 C geochronologies based on such samples, and such uncertainty may not have been fully considered in previous Baltic Sea studies. We quantify this uncertainty by analyzing bulk sediment 14 C determinations carried out on densely spaced intervals in independently dated late‐Holocene sediment sequences from two central Baltic Sea cores. Our results show a difference of 600 14 C yr in median bulk sediment reservoir age, or R ( t )bulk, between the two core locations ( 1200 14 C yr for one core, 620 14 C yr for the other), indicating large spatial variation. Furthermore, we also find large downcore (i.e., temporal) R ( t )bulk variation of at least 200 14 C yr for both cores. We also find a difference of 585 14 C yr between two samples taken from the same core depth. We propose that studies using bulk sediment 14 C dating in large brackish water bodies should take such spatiotemporal variation in R ( t )bulk into account when assessing uncertainties, thus leading to a larger, but more accurate, calibrated age range. Key Points: Bulk sediment 14 C ages show large variation across a short sediment sequence in two Baltic Sea cores An approximately 600 14 C yr difference in median bulk sediment reservoir age is noted between the two cores, indicating large spatial variation Additionally, downcore bulk sediment reservoir age variation of at least approximately 200 14 C yr is noted for both cores